2014
DOI: 10.1016/j.dam.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

On the bend-number of planar and outerplanar graphs

Abstract: The bend-number b(G) of a graph G is the minimum k such that G may be represented as the edge intersection graph of a set of grid paths with at most k bends. We confirm a conjecture of Biedl and Stern showing that the maximum bend-number of outerplanar graphs is 2. Moreover we improve the formerly known lower and upper bound for the maximum bend-number of planar graphs from 2 and 5 to 3 and 4, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…The bend number of classical graph classes was investigated as well. In [14], it was shown that outerplanar graphs are B 2 -EPG graphs and that planar graphs are B 4 -EPG graphs. For planar graphs, it is still an open question whether their bend number is equal to 3 or 4.…”
Section: Introductionmentioning
confidence: 99%
“…The bend number of classical graph classes was investigated as well. In [14], it was shown that outerplanar graphs are B 2 -EPG graphs and that planar graphs are B 4 -EPG graphs. For planar graphs, it is still an open question whether their bend number is equal to 3 or 4.…”
Section: Introductionmentioning
confidence: 99%
“…90 degrees turns at a grid-point) that the paths may have: a graph is a B k -VPG graph, for some integer k ≥ 0, if one can assign a path on a grid having at most k bends to each vertex such that two vertices are adjacent if and only if the corresponding paths intersect on at least one grid-point. Since their introduction, B k -VPG graphs have received much attention (see for instance [3,4,[8][9][10][11]17,19,21,22,24]).…”
Section: Introductionmentioning
confidence: 99%
“…90 degrees turns at a grid-point) that a path may have; for k ≥ 0, the class B k -EPG consists of those EPG graphs admitting a representation in which each path has at most k bends. Since their introduction, B k -EPG graphs have been extensively studied from several points of view (see for instance [1,2,3,5,6,7,8,9,14,15]). One major interest is the so-called bend number ; for a graph class G, the bend number of G is the minimum integer k ≥ 0 such that every graph G ∈ G is a B k -EPG graph.…”
Section: Introductionmentioning
confidence: 99%